A Decade of Research on Intergenerational Ties: Technological, Economic, Political, and Demographic Changes. Issue 1 (5th January 2020) - Fingerman, Karen L.; Huo, Meng; Birditt, Kira S.
Abstract: Due to extended transitions to adulthood and declining marital rates, bonds between adults and parents have grown increasingly salient in individuals' lives. This review organizes research around these topics to address ties between parents and grown children in the context of broader societal changes over the past decade. Literature searches included tables of contents of premier journals (e.g., Journal of Marriage and Family), Psychological Info, and Google Scholar. The literature review revealed patterns of social and intergenerational changes. Technological advances (e.g., introduction of the smart phone) co‐occurred with more frequent contact and interdependence between generations. The Great Recession and financial strains altered the nature of many parent/child ties, including increased rates of intergenerational coresidence. Individual life problems such as divorce, addiction, and physical health problems were reflected in complex changes in positive and negative relationship qualities, ambivalence, and intergenerational support. Government policies reflect societal values and in turn, affected the distribution of parents' and grown children's resources. Political disruptions instigated migration, separating generations across large geographic regions. Political disruptions instigated migration, separating generations across large geographic regions. Demographic changes (e.g., constellation of family members, delayed marriage, same sex marriage) were also manifest in ties between adults and parents. Findings were consistent with the Intergenerational Systems in Context Model, which posits that societal transformations co‐occur with changes in intergenerational relationships via reciprocal influences.